2014
DOI: 10.1002/anie.201405485
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for a Peroxide Intermediate and a Reactive Enzyme–Substrate–Dioxygen Configuration in a Cofactor‐free Oxidase

Abstract: Cofactor-free oxidases and oxygenases promote and control the reactivity of O2 with limited chemical tools at their disposal. Their mechanism of action is not completely understood and structural information is not available for any of the reaction intermediates. Near-atomic resolution crystallography supported by in crystallo Raman spectroscopy and QM/MM calculations showed unambiguously that the archetypical cofactor-free uricase catalyzes uric acid degradation via a C5(S)-(hydro)peroxide intermediate. Low X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 24 publications
(30 reference statements)
4
54
1
Order By: Relevance
“…Recent X-ray and neutron crystal structures of uricase binding with different inhibitors and UA have provided fundamental insights into the possible enzyme-substrate binding mode in the catalytic site of the enzyme. 11h–11k As revealed in the crystal structure of thermophilic Bacillus sp. TB-90 12 bound with inhibitor 8-azaxanthine, extensive electrostatic and hydrogen-bonding interactions with the inhibitor are contributed by highly conserved residues Arg201, Gln250, Asn276, and Gln304 from one subunit, and residues Thr73 and Asp74 from another subunit.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent X-ray and neutron crystal structures of uricase binding with different inhibitors and UA have provided fundamental insights into the possible enzyme-substrate binding mode in the catalytic site of the enzyme. 11h–11k As revealed in the crystal structure of thermophilic Bacillus sp. TB-90 12 bound with inhibitor 8-azaxanthine, extensive electrostatic and hydrogen-bonding interactions with the inhibitor are contributed by highly conserved residues Arg201, Gln250, Asn276, and Gln304 from one subunit, and residues Thr73 and Asp74 from another subunit.…”
Section: Introductionmentioning
confidence: 98%
“…The binding site of O 2 has also been determined to be at a site ~3 Å above the inhibitor and formed a hydrogen-bonding network with residues Asn276, Gln304, and Thr73 from the neighboring subunit. 11i,11k The X-ray structure of Aspergillus flavus uricase 11h in complex with UA and chloride ion (PDB entry of 3L9G with resolution of 1.75 Å) showed that the binding mode of UA with the uricase was very similar as the binding mode of 8-azaxanthine with Bacillus sp. TB-90 uricase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online Raman spectroscopy was performed on beamline ID29 as described previously (Bui et al, 2014) using a setup specifically designed for the collection of X-ray and Raman data in an interleaved manner (von Stetten et al, unpublished work). In brief, Raman spectra were recorded using an inVia Raman instrument (Renishaw PLC, Wotton-under-Edge, England) equipped with a near-infrared (785 nm) 300 mW diode laser source.…”
Section: Online Raman Spectroscopymentioning
confidence: 99%
“…Extensive computational details of the reaction mechanisms of coproporphyrinogen oxidase (Silva & Ramos, 2008) and vitamin K-dependent glutamate carboxylase (Silva & Ramos, 2007) confirmed that substrate deprotonation is indeed required for their catalytic action. Evidence for substrate deprotonation is also available for urate oxidase (Bui et al, 2014), although in this instance a more complex mechanism involving transient protein-based free radicals was proposed to be operative, based on EPR measurements of anaerobic preparations of substrate-bound enzyme (Gabison et al, 2011). Based on the reaction profile towards a superoxide-scavenging spin probe, radical-pair reactivity towards O 2 has also been suggested to occur (Thierbach et al, 2014) in a bacterial ring-cleaving 2,4-dioxygenase active towards (1 H )-3-hydroxy-4-oxoquinolines (EC 1.13.11.47), but recent computational results have been interpreted as contradicting this hypothesis, as the computed reaction energy for the electron transfer from substrate to O 2 (8–11 kcal  mol −1 ) would imply an “endothermic process […] unlikely to happen spontaneously in the protein or in solvent” (Hernández-Ortega et al, 2015).…”
Section: Introductionmentioning
confidence: 99%